St. Teresa Church postcard - Joe Stievak::::::author::: (Jerry Duchscherer, 1969)
Photo of the newly constructed church with a message written on the back, 'Hi - just came in for an affair at St. Teresa's - have been on campus stay at U.C.L.A. - introducing 5 dim. arts and science - love, Joe Stievak - Blessings and Health, the Codies'. Dated Aug. 24th, without year.